Clinical and Laboratory Profile of COVID-19 Patients Admitted at a Tertiary Care Center in New Delhi and Assessment of Factors Predicting Disease Severity - Piyush Jain; Nitin Sinha; M. K. Hari Prasad; Vaibhav Padole (Indian Journal of Medical Specialities)
Background: This study was conducted in nonintensive care unit COVID-19 patients admitted in a tertiary care center, to assess the clinical profile and find surrogate markers to predict the severity of COVID-19 at the time of admission. Methodology: It is a cross-sectional observational study. Clinical and laboratory data were compiled of patients admitted in COVID wards in a tertiary care center. Patients were stratified clinically according to the severity of COVID pneumonia. The admission clinical and laboratory parameters were compared between the severe and nonsevere COVID patients. Results: The study included 63 patients of which 46 were males, with a mean age of 47 years. Patients were classified into mild (32%), moderate (19%), and severe (49%) categories according to national guidelines. Fever (81%), cough (67%), and dyspnea (67%) were the most commonly observed symptoms. In comparative analysis, mean C-reactive protein (CRP), serum ferritin, and neutrophil–lymphocyte ratio (NLR) were significantly higher in severe COVID-19 patients and the admission PaCO2 significantly lower compared to nonsevere patients. Conclusion: The study shows that raised NLR, CRP, serum ferritin, and low PaCO2 levels at the time of admission are important predictors of disease severity.